Anaerobic Technology in Pulp and Paper Industry - Bajpai, Pratima; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents a state-of-the-art report on the treatment of pulp and paper industry effluents using anaerobic technology. It covers a comprehensive range of topics, including the basic reasons for anaerobic treatment, comparison between anaerobic and aerobic treatment, effluent types suitable for anaerobic treatment, design considerations for anaerobic treatment, anaerobic reactor configurations applied for treatment of pulp and paper industry effluents, present status of anaerobic treatment in pulp and paper industry, economic aspects, examples of full scale installations and future trends. .
Introduction -- Description of anaerobic digestion process -- Anaerobic versus aerobic treatment -- Effluent characteristics and treatability -- Design considerations for anaerobic treatment -- Anaerobic reactor configurations -- Anaerobic treatment of pulp and paper industry effluents -- Methods for removing sulphur compounds from the effluents -- Measures to render complex wastewaters more amenable to anaerobic treatment.-Example of Full-scale installations -- Economic comparison of anaerobic and aerobic process -- Future trends and perspectives.
Keywords: Chemistry, Technical; Refuse and refuse disposal; Manufactures; Industrial Chemistry; Waste Management/Waste Technology; Machines, Tools, Processes